1991
DOI: 10.1002/app.1991.070431110
|View full text |Cite
|
Sign up to set email alerts
|

The application of the iosipescu shear test to structural adhesives

Abstract: SYNOPSISThe Iosipescu shear test method, adapted for adhesives, was used to evaluate shear stressstrain properties of five epoxy-based film adhesives. The shear strength of some adhesives, determined by this technique, was found to differ greatly from that determined by either lap shear and/or thick adherend tests. Accurate measurements of the adhesive bond-line deformation enabled evaluation of the adhesive elastic and plastic properties as well as the calculation of shear modulus. A high-speed video camera w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Test results reported by Grabovac and Morris [17] showed that the shear strengths of brittle adhesives achieved using the Iosipescu specimen were greater than the strengths found from lap shear joint specimens, suggesting that the Iosipescu specimen has lower stress concentrations. The strengths obtained for tougher adhesives that experience shear yielding were comparable with those obtained by the other methods.…”
Section: Accuracy and Reliability Of The Iosipescu Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Test results reported by Grabovac and Morris [17] showed that the shear strengths of brittle adhesives achieved using the Iosipescu specimen were greater than the strengths found from lap shear joint specimens, suggesting that the Iosipescu specimen has lower stress concentrations. The strengths obtained for tougher adhesives that experience shear yielding were comparable with those obtained by the other methods.…”
Section: Accuracy and Reliability Of The Iosipescu Methodsmentioning
confidence: 99%
“…Typically, a bulk specimen for a rigid adhesive, such as an epoxy, would be a minimum of 4 mm wide, and the effects of exothermic heating during cure need to be considered when preparing very thick specimens. Joint specimens can be wider; 20 mm wide adherends are used often [17,18], since exothermic heating is less of an issue with metallic adherends and thin bondlines.…”
Section: Test Specimensmentioning
confidence: 99%
See 2 more Smart Citations